Comparative studies on the behavior of silk-worm hybrids - Souza, Celso F. de; Marques, Lúcia M. Queiroz; Abreu, Oldemar C.; Abramides, Pedro; Bonilha, Nivaldo A. (Pesquisa Agropecuaria Brasileira, 2014)
The authors present results from comparative regional studies on hybrids. These studies were conducted at the Seção Experimental de Sericicultura e Apicultura do Instituto de Pesquisas e Experimentação Agropecuárias do Centro-Sul in 1965. The characteristics studied were: cocoon production; silk quality; and thread production. Cocoon production by hybrids IS.117-IS.122 and IS.124-IS.117 was significantly greater than that of the other hybrids. There was no significant differences in thread production or silk quality.